Geriatric Syndromes and Abandonment - Abel Pérez Pavón; Alejandra Villegas Villegas; Yamileth del Socorro López Franco; Donovan Casas Patiño; Alejandra Rodríguez Torres (Revista Finlay)
Foundation: abandonment in old age is a condition of many health disorders and is, to a greater extent, a condition of high incidence worldwide. Objective: to compare geriatric syndromes and abandonment in older adult patients. Methods: a cross-sectional, descriptive, analytical and correlational study was carried out in the Family Medicine Unit No. 33 of the Mexican Social Security Institute of Tabasco. The sample was made up of 203 patients aged 60 and over, who attended Family Medicine and Continuing Medical Care consultations. Three instruments were applied: the Pfeiffer scale, the International Consultation on Incontinence Questionnaire Short-Form, the Perception of Abandonment Scale for the Elderly, and questions were asked about the consumption of prescribed and self-medicated medications. Results: there is a relationship between geriatric syndromes and abandonment, as verified in the correlation between the variables analyzed. Mild, moderate and severe cognitive impairment was found in low proportions. 40.7 % of the patients accepted having urinary incontinence. The presence of polypharmacy was found in high proportions. Conclusions: the geriatric syndromes present in the study such as: cognitive impairment, polypharmacy and urinary incontinence, plus the presence of being single, widowed or divorced show a significant relationship to suffering abandonment.